Optimization of self-sufficient hybrid renewable energy source fed BWRO desalting plant through fuzzy AHP and VIKOR MCDM techniques - D. Suriya kumari; P.S. Manoharan; K. Chidambarathanu; J. Vishnupriyan (Desalination and Water Treatment)
Water scarcity poses a top-tier challenge for numerous cities in India; elements like population density, industrial growth, and climate patterns compound this issue. A research paper has been put forth with the aim of conducting a thorough investigation into the enhancement of a self-sufficient brackish water reverse osmosis (BWRO) desalination facility empowered by non-depleting clean energy resources to address water scarcity in various climatic zones in the south of India. The facility is fabricated to yield clean water at a proportion of 1.0 m³ /h, catering to both household and commercial needs. Within this framework, the study explores three different setups - the base case, re-circulation, and energy recovery device (ERD) - to appraise an efficient BWRO plant. The Fuzzy Analytic Hierarchy Process (Fuzzy AHP) and Vlkriterijumsko KOmpromisno Rangiranje (VIKOR) methods are utilized for a thorough exploration of the significance in selecting the optimal configuration and size for establishing a BWRO plant. The key factors for the BWRO plant encompass the energy usage of the water pump, solar energy generation, cost per unit of consumable water, NPC, pH level of the water, and the community's familiarity with the area. Four distinct climatic regions are taken into account, and the most suitable configuration for each region is determined using Fuzzy AHP. Among the regions, Zone-II emerges as the preferred choice for installing a BWRO plant featuring a solar PV system, a battery, and an ERD scheme in its setups with the lowest power cost of 0.04$/m3 and supplies water at a cost of 0.42$/m3 accounting to overall power consumption of 0.26kWh/m3. The findings underscore the necessity of adaptable energy administration within the configurations and the financial limitations for sustainable water resource management in chosen regions with varying climatic circumstances.